SEMINAL ATTRIBUTES OF JAPANESE QUAIL IN ASSAM (Indian Journal of Animal Production and Management, 2015)
An experiment was conducted to record the basic information on seminal attributes of Japanese quail in agro climatic condition of Assam. Five male Japanese quails were taken for the study, reared in individual cages at room temperature (25 C) and the semen was collected twice-weekly by using massage method. Each ejaculate was evaluated for volume, sperm concentration, initial sperm motility, live sperm and sperm abnormality. The results revealed that mean ejaculate volume 0.04 ± 0.02, 0.02 ± 0.0, 0.05 ± 0.02, 0.01 ± 0.0 and 0.04 ± 0.02 ml; sperm concentration 750 ± 32.42, 736 ± 24.72, 749 ± 31.49, 728 ± 23.51 and 779 ± 33.41 million/ml; initial sperm motility 79.2 ± 1.08, 80.8 ± 1.28, 80.4 ± 1.31, 80.4 ± 1.12 and 81.3 ± 1.12 per cent; live sperm 85.1 ± 1.16, 87.4 ± 1.17, 85.9 ± 1.12, 85.1 ± 1.29 and 83.3 ± 1.45 per cent; sperm head abnormality 1.6 ± 0.32, 1.85 ± 0.22, 1.8 ± 0.27, 1.8 ± 0.22 and 1.75 ± 0.23 per cent; mid piece abnormality 0.82 ± 0.07, 0.82 ± 0.07, 0.82 ±0.07, 0.83 ± 0.07 and 0.99 ± 0.14 per cent; total tail abnormalities 3.44 ± 0.47, 4.0 ± 0.57, 4.24 ± 0.41, 3.44 ± 0.58 and 3.54 ± 0.47 per cent for bird I,II,III, IV respectively. Thus, the bird to bird variation in seminal attributes was found to be non significant.
Keywords: Japanese quail; seminal attributes; Assam